Sosialisasi Pencegahan Kekerasan Seksual di Lingkungan Sekolah Menengah Atas Negeri 15 Padang - Wahyu Pramono; Dwiyanti Hanandini; Nini Anggraini; Indah Sari Rahmaini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Schools become one of the secondary socialization agents that children get. Unfortunately, schools are a place that is prone to sexual violence. Therefore, it is necessary to socialize the prevention of sexual violence in schools so that schools become safe spaces for children to continue their education. This activity is beneficial for schools to raise awareness of the importance of preventing sexual violence. Service activities were conducted using counselling and focused group discussions—the place of activity at State High School 15, Padang. Prevention of sexual violence in schools can be done by empowering students to become agents of change. State High School 15, Padang, has an anti-bullying ambassador who can also function as an anti-sexual violence ambassador at school. Cases of sexual violence must be prevented by involving various parties, ranging from schools, students, and families. Socialization activities on anti-sexual violence values ​​need to be carried out continuously among school students so that they become part of their behaviour. Anti-sexual violence values ​​that have been internalized will make students behave spontaneously to reject acts of sexual violence.